The Influence of Digital Supply Chain on Operational Performance: A Case Study at Food and Beverage Industry in Malaysia - Ku Yong Quan,; Hafizah Zulkipli, (Research in Management of Technology and Business, 2024)
This study investigates the impact of digital supply chain (DSC) on operational performance in the food and beverage industry in Malaysia. With the rapid advancement of digitalization, companies in this industry are increasingly adopting these technologies to improve their supply chain operations. However, there is a lack of comprehensive research specifically focusing on the Malaysian food and beverage sector. Thus, this research aims to address this gap by examining the current level of operational performance and analyzing the relationships between digital supply chain and operational performance. The research objectives include assessing the extent of operational performance, investigating the connection between big data analytic and operational performance, and examining the relationship between internet of things and operational performance. The study will target companies in the food and beverage industry in Malaysia and will be conducted within this specific context. The findings of this research have revealed that big data analytic and internet of things have positive significant influence on operational performance in food and beverage industry in Malaysia. The value of determination coefficient correlation between big data analytic, internet of things, and operational performance shows a positive correlation.